Digitalização da História da Música Popular Brasileira (1982), da Abril Cultural - Pinheiro, Amanda Oliveira [UNESP]; Simões Júnior, Álvaro Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The extension research aim the scanning process of the collection “História da Música Popular Brasileira”, that was sell in newsstands in the begins of de decade of 1980 by the publisher Abril Cultural. We pretend put at disposition of the users of ‘Centro de Documentação e Apoio à Pesquisa (CEDAP)’ materials that encompass an important patrimony of Brazilian’s culture. Researchers and professors of all different levels of teaching can consult files in form PDF that correspond to booklets and can listen the different soundtrack in CEDAP’s computers also. Do this in this way the consults of the collection becomes more quick and easy and don’t expose the albums to inevitable damages for the frequently action the time.

O projeto de extensão visa à digitalização da coleção “História da Música Popular Brasileira” que foi vendida em bancas de jornal no início da década de 1980 pela editora Abril Cultural. Pretende-se colocar à disposição dos usuários do Centro de Documentação e Apoio à Pesquisa (CEDAP) materiais que abrangem um importante bem cultural brasileiro. Pesquisadores e docentes dos diferentes níveis de ensino podem consultar arquivos no formato PDF que correspondem aos encartes dos álbuns e podem também ouvir as diferentes trilhas sonoras nos computadores do Cedap. Dessa forma, a consulta à coleção torna-se muito rápida e não se expõem os álbuns a danos inevitáveis frequentes.
Keywords: Brazilian popular music; Publisher Abril; History of MPB; Música popular brasileira; Editora Abril; História da MPB